STEM and Social Sciences Students’ Language-Oriented Academic Challenges in English Medium of Instruction (EMI) Programs: The Case of An International University in Kazakhstan - Karabay, Akmaral (Nazarbayev University Graduate School of Education, 2017)
English Medium of Instruction (EMI), that is teaching subjects in English, is becoming a new phenomenon across Kazakhstani Higher Education. However, students have the language challenges when studying in English since it is not their first language. Therefore, the study has investigated STEM (i.e. Science Technology Engineering and Mathematics) and Social sciences students‟ perceptions on choosing EMI and language challenges in EMI academic environment in an international university whose practices can be translated to other state universities newly implementing EMI. The research questions that guided study are as follows: What are STEM and Social sciences students‟ and teaching administrative staff perceptions of EMI and how do they describe and address the students‟ language challenges in academic contexts in EMI programs? The study is drawn upon qualitative case study research design employing interviews with 3 teaching-administrative staff members from 3 departments (2 STEM and 1 social sciences school), 1 university administrator as well as 1 focus group and 7 in-depth interviews with students. The data indicate that STEM and social sciences students have different level of language challenges. However, what was similar across the majors is that their challenges were mostly oriented on writing and speaking. Professors showed their awareness about the language challenges of students, although their understanding differed a bit in some details such as the nature of listening challenges caused by professors‟ language deficiency. In contrast, support provided by university and professors reportedly addresses students‟ academic difficulties during their studies. Yet, unlike social sciences, in STEM areas students are less likely to get their language improved by the end of their studies. Overall, the study suggest professors to interact with students more to learn and address students‟ language challenges. As EMI cannot guarantee students‟ English improvement, students may enhance the language by creating English environment around themselves.
Keywords: social sciences students; Language-Oriented Academic Challenges; English Medium of Instruction; international university; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; STEM subjects